Improving the adoption of stress tolerant maize varieties using social ties, awareness or incentives: Insights from Northern Benin (West-Africa) - Adechian, S.A.; Baco, M.N.; Abdoulaye, T. (Elsevier, 2023)
Maize is the staple food of most households in sub-Saharan Africa. The adoption of stress-tolerant maize varieties (STMV) is being promoted due to climate change. There are various methods applied to disseminate these varieties. Unfortunately, the adoption at the household level is still unsatisfactory. This study evaluated the effectiveness of the dissemination methods used in Benin. We identified dissemination methods from key informants involved in STMV seed dissemination projects. The performance of the identified methods was assessed through the perceptions of 150 maize-farming households using the Likert scale. We assessed the extent to which each method leads to the knowledge, use, and continued use (appropriation) of STMV seeds. Friedman and Wilcoxon rank tests were used for data analysis. Nine dissemination methods were identified and categorized into four groups according to their theoretical driven: strengthening social ties, capacity building, incentive, and awareness raising. Our results revealed that dissemination methods that focus on strengthening social ties, raising awareness, and providing incentives are more effective in promoting STMV adoption. Depending on the intended adoption (awareness, use, and appropriation), extension services and STMV promotional projects could focus on strengthening social ties, raising awareness, and providing incentives. However, future research must identify which of the methods leads to a higher rate of adoption of STMV.